Study and Analysis of Routing and Spectrum Allocation (RSA) and Routing, Modulation and Spectrum Allocation (RMSA) Algorithms in Elastic Optical Networks (EONs) - Shirin Abkenar, Forough; Ghaffarpour Rahbar, Akbar (Optical switching and networking, 2017)
With the growth of Internet users' traffic demands, the efficient and cost-effective usage of bandwidth and spectrum in optical networks plays an important role in improving service provisioning. An Elastic Optical Network (EON) is a new generation of optical networking that can provide high flexibility and scalability in spectrum allocation and data rate accommodation to support different traffic types. In fact, EON can allocate the available resources in a network according to users' demands. Besides, EON generates elastic optical paths (the paths with variable bit rates) and divides available spectrum flexibly according to the traffic demands of users. This study reviews and analyzes one of the most important topics in EON namely Routing and Spectrum Allocation (RSA). In fact, RSA selects the most appropriate resources according to the conditions of the resources and flexibility assigns them to the connection demands. RSA can be divided into two categories: without adjusting modulation format (simply referred to as RSA) and with adjusting modulation format (called Routing, Modulation and Spectrum Allocation, RMSA). In this paper, we review all available RSA and RMSA algorithms proposed for EON, analyze and compare them through both quality of performance and computational complexity aspects for the first time.